Keterlibatan Dukun Bayi Dalam Pertolongan Persalinan - Ike Putri Setyatama; Sucy Khilmi; Alfina Damayanti; Nabiilah Nafa Labiibah (Universitas Muhammadiyah Pekajangan Pekalongan, 2023)
One of the Sustainable Development Goals is to reduce the Maternal Mortality Rate in 2030 to 70 deaths per 100,000 live births. In 2022 the number of deliveries in Tegal Regency is 26,679 (96.41%) vaginal deliveries 26,282 (95.6%) assisted by health workers in health care facilities 241 (0.9%) are in non-health care facilities 156 (0 .6%) assisted by non-medical health workers. In 2022, 13 maternal deaths are dominated by 60% postpartum hemorrhage, 20% embolism, 10% edema, and others. The Bumijawa Community Health Center is the largest number of delivery assistance places in Tegal Regency. In 2022 there will be 1,685 vaginal deliveries consisting of 87.7% health workers and 5% non-health workers; even though the target is 97%. The purpose of this study was to determine the involvement of traditional birth attendants in assisting with childbirth. Data collection was carried out by in-depth interviews and data reduction, demonstrated by narration, using the triangulation method, and analyzed by saturated samples. The research informants were 3 mothers who had given birth with a dukun as the main informant, 3 dukun and a midwife as triangulation informants. The results showed that the mother's decision to choose birth attendants was related to experience, knowledge, attitudes, access to services, husband and family support, local culture; This can be seen from the level of public awareness of health which is still low